Non-enhanced phytoextraction of cadmium, zinc, and lead by high-yielding crops - Mayerová, Markéta; Petrová, Šárka; Madaras, Mikuláš; Lipavský, Jan; Šimon, Tomáš; Vaněk, Tomáš (Environmental science and pollution research international, 2017)
Heavy metal soil contamination from mining and smelting has been reported in several regions around the world, and phytoextraction, using plants to accumulate risk elements in aboveground harvestable organs, is a useful method of substantially reducing this contamination. In our 3-year experiment, we tested the hypothesis that phytoextraction can be successful in local soil conditions without external fertilizer input. The phytoextraction efficiency of 15 high-yielding crop species was assessed in a field experiment performed at the Litavka River alluvium in the Příbram region of Czechia. This area is heavily polluted by Cd, Zn, and Pb from smelter installations which also polluted the river water and flood sediments. Heavy metal concentrations were analyzed in the herbaceous plants' aboveground and belowground biomass and in woody plants' leaves and branches. The highest Cd and Zn mean concentrations in the aboveground biomass were recorded in Salix x fragilis L. (10.14 and 343 mg kg-1 in twigs and 16.74 and 1188 mg kg-1 in leaves, respectively). The heavy metal content in woody plants was significantly higher in leaves than in twigs. In addition, Malva verticillata L. had the highest Cd, Pb, and Zn concentrations in herbaceous species (6.26, 12.44, and 207 mg kg-1, respectively). The calculated heavy metal removal capacities in this study proved high phytoextraction efficiency in woody species; especially for Salix × fragilis L. In other tested plants, Sorghum bicolor L., Helianthus tuberosus L., Miscanthus sinensis Andersson, and Phalaris arundinacea L. species are also recommended for phytoextraction.
Keywords: průmyslová hnojiva; Minimum inputs; Metals, Heavy; látky znečišťující půdu; Zinc; Malva; Agriculture; olovo; Biodegradation, Environmental; biodegradace; zemědělství; Lead; těžké kovy; Soil contamination; Soil Pollutants; Cadmium; Fertilizers; Heavy metals; Phytoextraction; kadmium; Field trial; zinek